Comparing robotic surgery with laparoscopy and laparotomy for endometrial cancer management: A cohort study. (January 2015) - Chiou, Hung-Yi; Chiu, Li-Hsuan; Chen, Ching-Hui; Yen, Yuan-Kuei; Chang, Ching-Wen; Liu, Wei-Min
Abstract: Introduction : Robotic surgery has been applied in managing various types of gynecologic cancers. The purpose of this study is to compare the surgical outcomes of robotic surgery, laparoscopy and laparotomy for managing endometrial cancer.Methods : A total of 365 patients received surgical staging for treating IA to IIIC endometrial cancer were retrospectively enrolled. Patient demography, peri-operative parameters, and survival outcomes were studied.Results and discussions : Robotic surgery showed a significant lower blood loss and 24-h pain score as compared to other surgical types. Moreover, compared to laparotomy, robotic and laparoscopic surgeries were associated with reduced operation time, decreased time to full diet resumption, and shortened hospital stay. No significant differences were found between the groups in terms of overall complication rate. Eighteen-month follow-up of the patients indicated no significant differences in disease-free survival and overall survival.Conclusion : Compared to conventional approaches, robotic surgery showed favorable short-term outcomes with comparable survival. It is suggested that robotic surgery is a feasible tool for endometrial cancer management. Highlights: Robotic surgery has been applied in managing various types of gynecologic cancers. Robotic surgery showed favorable short-term results in treating endometrial cancer. Robotic surgery showed similar complication rate to laparoscopy and laparotomy. Robotic surgery showed comparable survival outcomes to laparoscopy and laparotomy.